Analysis Of Large In-Plane Displacement And Strain In Rubber Using 2-D Scanner-Based Digital Image Correlation - Pang, Goh Ching (2017)
Various digital image correlation (DIC) techniques have been introduced in the past to solve the limited field-of view (FOV) problem for large deformation measurement. However, these methods share a common limitation which is low FOV. In this research, a novel two-dimensional scanner-based digital image correlation (2-D SB-DIC) method that enables the acquisition of a large FOV of an unfilled natural rubber (uNR) specimen at large deformation has been developed. The images were scanned and processed to obtain displacement, strain, load and stress data. The displacement data were obtained by using the incremental image correlation algorithm. The mean of the tangent and secant moduli of the uNR specimen obtained from the 2-D SB-DIC method from five repeated experiments were compared with those obtained from a universal testing machine (UTM). A new algorithm for mapping large deformation in the uNR specimens in a single-step without the need for a series of deformation images has also been developed. The axial strains obtained by using the proposed single-step 2-D SB-DIC algorithm were compared with those obtained using the conventional incremental image correlation algorithm. Non-homogeneous strain distribution tests were also conducted by analysing the deformation of two rectangular rubber specimens containing circular and square holes using the single-step 2-D SB-DIC algorithm. The resultant strain maps for the ; specimens were compared with those from finite element modelling (FEM). The Young‟s moduli obtained by using the incremental 2-D SB-DIC algorithm showed maximum absolute errors of 9.5% at 250% axial strain and 4.2% at 50% axial strain in tangent modulus and secant modulus, respectively. Meanwhile the maximum deviation of the Poisson‟s ratio based on engineering strain and true strain up to the threshold value of incompressibility behaviour for polymeric material are only 1.36% and 1.24%, respectively. A maximum absolute deviation of 10.7% at axial strains of 320% was found by using the proposed single-step 2-D SB-DIC algorithm. For the non-homogeneous strain distribution tests, the comparison of the resultant strain maps showed that the proposed single-step algorithm coupled with the 2-D SB-DIC method can be used to map the strain accurately in large deformation materials like rubber. The single-step 2-D DIC algorithm eliminates the cumulative error introduced in the incremental 2-D DIC algorithm while reducing processing time in image acquisition and image correlation tremendously.